EFFECT OF DIETARY PROTEIN AND ENERGY ON GROWTH OF JUVENILE HUMPBACK GROUPER (CromiIeptes altivelis) - Nyoman Adiasmara Giri; Ketut Suwirya; Muhammad Mazuqi (Indonesian Fisheries Research Journal, 2002)
The effect of varying protein and energy contents of diet on the groMh and nutrient retention of juvenile humpback grouper was examined using a 3 x 3 factorial design with three replicates.